Microenvironmental Ecology of the Chlorophyll b-Containing Symbiotic Cyanobacterium Prochloron in the Didemnid Ascidian Lissoclinum patella - Kühl, Michael; Behrendt, Lars; Trampe, Erik C.; Qvortrup, Klaus; Schreiber, Ulrich; Borisov, Sergey M.; Klimant, Ingo; Larkum, Anthony W. D. (Frontiers in Microbiology, 2012)
The discovery of the cyanobacterium Prochloron was the first finding of a bacterial oxyphototroph with chlorophyll (Chl) b, in addition to Chl a. It was first described as Prochloron didemni but a number of clades have since been described. Prochloron is a conspicuously large (7-25 µm) unicellular cyanobacterium living in a symbiotic relationship, primarily with (sub-) tropical didemnid ascidians; it has resisted numerous cultivation attempts and appears truly obligatory symbiotic. Recently, a Prochloron draft genome was published, revealing no lack of metabolic genes that could explain the apparent inability to reproduce and sustain photosynthesis in a free-living stage. Possibly, the unsuccessful cultivation is partly due to a lack of knowledge about the microenvironmental conditions and ecophysiology of Prochloron in its natural habitat. We used microsensors, variable chlorophyll fluorescence imaging and imaging of O2 and pH to obtain a detailed insight to the microenvironmental ecology and photobiology of Prochloron in hospite in the didemnid ascidian Lissoclinum patella. The microenvironment within ascidians is characterized by steep gradients of light and chemical parameters that change rapidly with varying irradiances. The interior zone of the ascidians harboring Prochloron thus became anoxic and acidic within a few min of darkness, while the same zone exhibited O2 super-saturation and strongly alkaline pH after a few min of illumination. Photosynthesis showed lack of photoinhibition even at high irradiances equivalent to full sunlight, and photosynthesis recovered rapidly after periods of anoxia. We discuss these new insights on the ecological niche of Prochloron and possible interactions with its host and other microbes in light of its recently published genome and a recent study of the overall microbial diversity and metagenome of L. patella.